PERAN TIM TEKNIS PADA PENGENDALIAN PROYEK PEMBANGUNAN MASJID PEMDA KOTA BENGKULU TAHAP I - HENDRA OKTA (Universitas Bengkulu, 2024)
In the 2022 Fiscal Year, the Bengkulu City Government is building a place of worship, namely the Bengkulu City Government Mosque, which is an iconic mosque in the red and white office complex which will accommodate ASN and the surrounding community. The research methods used are qualitative and quantitative methods, by examining various primary and secondary data collected, this case study produces the role of the Technical Team in the success of project development later.